Truncated FGFR2 is a clinically actionable oncogene in multiple cancers - Zingg, D; Bhin, J; Yemelyanenko, J; Kas, SM; Rolfs, F; Lutz, C; Lee, JK; Klarenbeek, S; Silverman, IM; Annunziato, S; Chan, CS; Piersma, SR; et al. (Springer Nature, 2022)
Somatic hotspot mutations and structural amplifications and fusions that affect fibroblast growth factor receptor 2 (encoded by FGFR2) occur in multiple types of cancer1. However, clinical responses to FGFR inhibitors have remained variable1,2,3,4,5,6,7,8,9, emphasizing the need to better understand which FGFR2 alterations are oncogenic and therapeutically targetable. Here we apply transposon-based screening10,11 and tumour modelling in mice12,13, and find that the truncation of exon 18 (E18) of Fgfr2 is a potent driver mutation. Human oncogenomic datasets revealed a diverse set of FGFR2 alterations, including rearrangements, E1–E17 partial amplifications, and E18 nonsense and frameshift mutations, each causing the transcription of E18-truncated FGFR2 (FGFR2ΔE18). Functional in vitro and in vivo examination of a compendium of FGFR2ΔE18 and full-length variants pinpointed FGFR2-E18 truncation as single-driver alteration in cancer. By contrast, the oncogenic competence of FGFR2 full-length amplifications depended on a distinct landscape of cooperating driver genes. This suggests that genomic alterations that generate stable FGFR2ΔE18 variants are actionable therapeutic targets, which we confirmed in preclinical mouse and human tumour models, and in a clinical trial. We propose that cancers containing any FGFR2 variant with a truncated E18 should be considered for FGFR-targeted therapies.